ANTI-MA2 ANTIBODIES IN A PATIENT WITH UPBEAT NYSTAGMUS. (29th November 2012) - Garcia-Reitboeck, P; MacDonald, M; Thompson, G; Omer, S; Griffin, C
Abstract : Ma2 antibodies are found in paraneoplastic disorders. These usually present as isolated or combined limbic and brainstem encephalitis. Case report: A 63-year-old lady presented with progressive dizziness, difficulty focusing while reading or watching TV, and unsteadiness, all of which had progressed over a period of 8 weeks. She was initially admitted with acute pancreatitis, which resolved with treatment. There was no associated weight loss or other signs of malignancy. She had been diagnosed with coeliac disease 17 years ago and she remained asymptomatic on a gluten-free diet. Neurological examination revealed marked upbeat nystagmus in all directions of gaze, most pronounced on downward gaze, in the absence of ataxia. MRI brain and initial CSF examination were normal. Oligoclonal bands were detected in both serum and CSF. Anti-Ma2 were identified in the serum, while other onco-neural and coeliac antibodies were negative. An extensive search for malignancy including whole body CT and PET, transvaginal US, mammography and colonoscopy has so far not identified a tumour. Upper GI endoscopy showed partial villous atrophy consistent with treated coeliac disease. The patient was initially treated with IV steroids without improvement and showed modest clinical improvement following plasma exchange. In conclusion, upbeat nystagmus can be associated with anti-Ma2 antibodies. Extensive workup has so far not identified a malignancy in our patient. Our patient showed modest clinical improvement after plasma exchange.